HISTOLOGICAL ASSESSMENT FOR THE EFFECT OF USING BACON ON THE SKIN OF FEMALE RATS (Academicia Globe: Inderscience Research, 2022)
The article emphasizes the special role of the factors of the competence-based approach in the development of the professional and ethical culture of young teachers, analyzes the main problems and factors that contribute to the development of ethical education by the teacher in modern conditions, and highlights the factors that underlie the professional and ethical culture of the teacher.